Control of Hard to Manage Weeds along Highway Rights-of-Way - Jason Ferrell; Ken Langeland (EDIS)
SS-AGR-275, a 4-page fact sheet by Jason Ferrell and Ken Langeland, provides two tables of recommendations for control of upland weeds and aquatic vegetation. Published by the UF Department of Agronomy, September 2007.